Experiência ontológica e tradição na experiência de guardiões de memórias - Roberta Vasconcelos Leite (2015)
In the contemporary world, the bond with the past is analyzed as something to be overcome and the most characteristic expressions of the subjects tend to be read as processes of invention of its own subjectivity. In this scenario, the human science productions that dedicates to themes such as the subject's perception about itself or the tradition tend to take them as antagonistic processes, making it difficult to understand the case of guardians of contemporary memories: subjects that in a personal movement decide to devote themselves to something that comes from the past, structuring works that takes care of memories. In this paper we investigate how is configured the relationship between ontological experience and tradition in the elaboration of the experience of people who are dedicated to cultural preservation in contemporaneity. Placing us in the field of culture psychology, we conducted an empirical research adopting Classical Phenomenology (Husserl and Stein) as our theoretical-methodological reference. For data collection, we select intentionally four subjects whose dedication to memories structured works of preservation with social incidence in various spheres (family, community, artistic, political) in different regions of Brazil. We performed semi-structured interviews which were textualized as narratives. Each was phenomenologically analyzed in four thematic axes: elaboration of the work of preservation; the emerge of personhood and the ontological experience; the development of tradition; the relationship between ontological experience and tradition in the elaboration of the experience. We recognized the essential elements of that relationship in the four analyzed interviews, building one type-experience. At a certain point in its trajectory, the person amazes itself with something that comes from the past and recognizes itself called to take care of it. Responding affirmatively to this call through a work, the person has the opportunity to elaborate the past and the otherness as presences from what it realizes its own being. Dedicate to what comes from the other emerges then as to be faithful to its own experience, opening the way for the update of the tradition in a personal process of seeking to contribute to the constitution of the world through his work of preservation. Experiencing personal realization, the person deals with obstacles and accepts sacrifices reaffirming the radical care of which the person founds itself called to do. Taking care to give continuity and passing on what was transmitted, in its own way, the person reaffirms the centrality of values that converge in an ideal aroused by tradition in it. With this ideal the person assesses other traditions and its own gesture of preservation, evidencing possibilities and limits. Realizing that its ideal was given to it and overcomes itself, the person lives its work as gratitude to which was offered, given itself to something that creates a place in the world and fulfill their own self. In the discussion of these results, we were able to point out how the relationship between ontological experience and tradition in the elaboration of the guardians of memories is structured as a recognition of a personal mission addressed to the affirmation of an ideal aroused by tradition itself. Declaring its own experience as a place of recognition of meaning, the person takes the ideal as impetus to formulate and fix its projects and engage itself so they can be rooted in the tradition’s values as a correspondence to its own being and to the world. We concluded this paper indicating how the analysis of these experiencies documented paths of how tradition takes place in the contemporary world, questioning approaches that discuss subjectivity in a necessarily individualistic way and causing us to consider implications that point to the memory care being personally correspondent in the present day.